Evaluation of engagement with hyperlocal e-participation systems by citizens and representatives - Cruickshank, Peter (Edinburgh Napier University, 2021)
This work is concerned with the information practices associated with hyperlocal representation. The findings derive from an evaluation of a portfolio of ten previously published papers covering the period 2010-2020.

The main contributions are: (a) The development of the concept of hyperlocal representation as a domain with its own challenges; (b) The characterisation of hyperlocal representatives as stakeholders in the participation process; and (c) Expansion of the existence and nature of lurkers as passive participants in the participation process, and the responses seen in the information sharing practices of the hyperlocal representatives, including use of information sharing by proxy. These contributions are significant because they are the first to consider community councillors as information actors in their own right, and their response to lurking behaviours in their community. This is in contrast with previous research at this level of government, which has focussed on the activities of citizens, and local government administration staff.

The portfolio demonstrates the application of frameworks derived from information science to the field of e-participation. It identifies the impact of the project- and information systems-based nature of much e-participation research, and proposes an information-centric perspective from information science to support a new analysis, through application of theoretical approaches derived from everyday life information practice, information literacy, activity systems and communities of learning. An additional contribution is the creation of a new model of the transition from lurking to participation based on social-cognitive theory. A further contribution of the thesis is to methodologies in information science, in particular through the design of questionnaires and supporting interviews as data collection instruments in this context.

This thesis adds to understanding of information sharing in a quasi-work context where there are limited expectations of interaction. It could support future research into the information practice of representatives in (a) the choice of channels for communication with citizens, (b) the information communities involved in the representation role and (c) the impact of the policy cycle on information practices.